2005
DOI: 10.1124/mol.105.015164
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Zinc Potentiation on the α4 Subunit of Neuronal Nicotinic Receptors

Abstract: We have shown previously that the function of neuronal nicotinic acetylcholine receptors can be modulated by zinc. This modulation varies from potentiation to inhibition, depending on receptor subunit composition and zinc concentration, with the ␣4␤2 and ␣4␤4 receptors displaying the most dramatic potentiation. In this study, we used site-directed mutagenesis to identify glutamate 59 and histidine 162 on the rat ␣4 subunit as potential mediators of zinc potentiation. By modeling the extracellular domain of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 42 publications
(84 reference statements)
5
41
1
Order By: Relevance
“…This region coincides with residues that have been shown to bind Ca 2+ in AChBP (Brejc et al 2001). Zinc-binding sites have been located at subunit interfaces in nAChR and GlyR (Hsiao et al 2006 ;Nevin et al 2003), while in GABA A receptors, zinc binds to both the ECD and the pore (Dunne et al 2002 ;Fisher & Macdonald, 1998 ;Fisher, 2002 ;Horenstein & Akabas, 1998 ;Hosie et al 2003). Binding of these ions is likely to have important physiological consequences although these are not yet fully understood.…”
Section: Ions As Modulatorsmentioning
confidence: 99%
“…This region coincides with residues that have been shown to bind Ca 2+ in AChBP (Brejc et al 2001). Zinc-binding sites have been located at subunit interfaces in nAChR and GlyR (Hsiao et al 2006 ;Nevin et al 2003), while in GABA A receptors, zinc binds to both the ECD and the pore (Dunne et al 2002 ;Fisher & Macdonald, 1998 ;Fisher, 2002 ;Horenstein & Akabas, 1998 ;Hosie et al 2003). Binding of these ions is likely to have important physiological consequences although these are not yet fully understood.…”
Section: Ions As Modulatorsmentioning
confidence: 99%
“…Although advances have been made in identifying Zn 2ϩ sites on GABA A (Hosie et al, 2003) and glycine (Miller et al, 2005a,b) receptors, corresponding sites on ␣4␤2 receptors have been relatively unexplored. A potentiating Zn 2ϩ -binding site has been proposed on ␣4␤4/␤2 nAChRs that involves Zn 2ϩ coordination by a histidine residue (␣4 H162 ) and a less direct, probably structural, contribution from ␣4 E59 (Hsiao et al, 2006). The site is likely to reside on the ␤2(ϩ)/ ␣4(Ϫ) subunit interfaces that alternate with the ACh-binding ␣4(ϩ)/␤2(Ϫ) subunit interfaces (Hsiao et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…A potentiating Zn 2ϩ -binding site has been proposed on ␣4␤4/␤2 nAChRs that involves Zn 2ϩ coordination by a histidine residue (␣4 H162 ) and a less direct, probably structural, contribution from ␣4 E59 (Hsiao et al, 2006). The site is likely to reside on the ␤2(ϩ)/ ␣4(Ϫ) subunit interfaces that alternate with the ACh-binding ␣4(ϩ)/␤2(Ϫ) subunit interfaces (Hsiao et al, 2006). Given that ␤2(ϩ)/␣4(Ϫ) interfaces are present on both receptor forms, receptor stoichiometry should not influence Zn 2ϩ effects on ␣4␤2 receptors (Hsiao et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This is not unique to Cl À inhibitory channels because a 4 b 4 nACh receptors are also potentiated by interaction of Zn 2þ with residues located at alternating a 4 b 4 interfaces (Hsiao et al, 2006). Similarly, other studies have demonstrated the presence of residues important for the potentiation of GlyRs by extracellular acting ligands.…”
Section: Residues Important For Agonist Binding and Modulationmentioning
confidence: 87%